2012
DOI: 10.1089/aid.2011.0278
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Mutations in HIV Type 1 Isolates from Patients Failing Antiretroviral Therapy in Morocco

Abstract: The emergence of viral-resistant strains is a major problem for the medical management of HIV-infected individuals. The aim of this study was to characterize viral subtypes and drug-resistance mutations (DRMs) in HIV-1 isolates from patients failing antiretroviral therapy (ART). A total of 45 HIV-1-infected patients failing ART were enrolled. The viral RT and Prot genes were amplified and sequenced to determine subtypes and potential DRMs. The subtype distribution was 74% subtype B, 11% subtype A, 9% CRF02-AG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…CRF06_cpx is the second most prevalent strain of HIV‐1 isolated in our study and was found at a similar frequency in Niger [Mamadou et al, ]. In contrast, only one subtype B strain was identified in Mauritania, although it is still the major variant circulating in the northern neighboring countries such as Algeria, Morocco and Tunisia [Mumtaz et al, ; El Annaz et al, ]. A rate of 15.4% of unique recombinant forms were also found with a similar rate to that reported in Senegal [Thiam et al, ], but lower than the one reported in Mali [Maiga et al, ].…”
Section: Discussionsupporting
confidence: 86%
“…CRF06_cpx is the second most prevalent strain of HIV‐1 isolated in our study and was found at a similar frequency in Niger [Mamadou et al, ]. In contrast, only one subtype B strain was identified in Mauritania, although it is still the major variant circulating in the northern neighboring countries such as Algeria, Morocco and Tunisia [Mumtaz et al, ; El Annaz et al, ]. A rate of 15.4% of unique recombinant forms were also found with a similar rate to that reported in Senegal [Thiam et al, ], but lower than the one reported in Mali [Maiga et al, ].…”
Section: Discussionsupporting
confidence: 86%
“…It was selected by lamivudine (3TC), emtricitabine (FTC) or ABC use and 3TC resistance with high level 24. This result was more highly observed than other mutations similar to the findings of other studies: Winand et al (M184V: 44.0%, n=3,554)25 and El Annaz et al (M184V: 44.0%, n=45) 26. This finding can be explained by the M184V mutation in line with lamivudine (3TC) resistance 27.…”
Section: Discussionsupporting
confidence: 90%
“…According to previous Moroccan studies, the prevalence of resistance to NRTIs, NNRTIs and PIs are continuously increasing among drug-naïve and treatment experienced patients [ 2 4 ], thus, developing new drugs for AIDS treatment would be needed.…”
Section: Introductionmentioning
confidence: 99%